α-Synuclein Gene May Interact with Environmental Factors in Increasing Risk of Parkinson's Disease - Gatto, Nicole M. (S. Karger AG, 2010)
BACKGROUND: Although of great interest and suggested in prior reports, possible α-synuclein (SNCA) gene-environment interactions have not been well investigated in humans. METHODS: We used a population-based approach to examine whether the risk of Parkinson's disease (PD) depended on the combined presence of SNCA variations and two important environmental factors, pesticide exposures and smoking. RESULTS/CONCLUSIONS: Similar to recent meta- and pooled analyses, our data suggest a lower PD risk in subjects who were either homozygous or heterozygous for the SNCA REP1 259 genotype, and a higher risk in subjects who were either homozygous or heterozygous for the REP1 263 genotype, especially among subjects with an age of onset ≤68 years. More importantly, while analyses of interactions were limited by small cell sizes, risk due to SNCA variations seemed to vary with pesticide exposure and smoking, especially in younger onset cases, suggesting an age-of-onset effect.